1987
DOI: 10.1177/036354658701500508
|View full text |Cite
|
Sign up to set email alerts
|

The percutaneous lateral retinacular release

Abstract: This study reviews 34 of 37 original patients who were reviewed in 1981 after previously undergoing percutaneous lateral retinacular release. Short-term satisfactory results regarding reduction of pain and prevention of dislocation were maintained on this second followup (average, 48 months). With this increase in postoperative time, patients with recurrent subluxation developed an increase in patellar slipping. Patients with chondromalacia and degenerative joint disease are less suited for long-term treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
5

Year Published

1990
1990
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(15 citation statements)
references
References 23 publications
0
10
0
5
Order By: Relevance
“…Ein offenes oder arthroskopisches laterales Release hat sich ebenfalls nicht als suffiziente Methode zur Behandlung chronischer patellofemoraler Instabilitä-ten oder rezidivierender Patellaluxationen erwiesen [4]. Zudem kommt es durch das laterale Release zu einer vermehrten patellofemoralen Instabilität [7].…”
Section: Anatomische Rekonstruktion Des Medialen Patellofemoralen Banunclassified
“…Ein offenes oder arthroskopisches laterales Release hat sich ebenfalls nicht als suffiziente Methode zur Behandlung chronischer patellofemoraler Instabilitä-ten oder rezidivierender Patellaluxationen erwiesen [4]. Zudem kommt es durch das laterale Release zu einer vermehrten patellofemoralen Instabilität [7].…”
Section: Anatomische Rekonstruktion Des Medialen Patellofemoralen Banunclassified
“…Similarly, 17 of 18 knees initially Correlation of postoperative results with preoperative findings rated good remained in that category. The conclusion from this is that a patient with an initial good or excellent result 1 year after open lateral release will most likely retain that rating for some years (Table 4). Patients with bilateral procedures all had good to excellent results.…”
Section: Resultsmentioning
confidence: 99%
“…MPS was first described in 1987 by Betz et al as a complication of lateral retinacular release [10]. Since then, Hughston et al reported medial subluxation in 50% of knees with recurrent patellar dislocation in which arthroscopic lateral retinacular release was performed [11].…”
Section: Discussionmentioning
confidence: 99%